<h3>
Answer: f( h(x) ) = 2x - 4</h3>
Work Shown:
f(x) = x - 7
f( h(x) ) = h(x) - 7
f( h(x) ) = 2x+3 - 7
f( h(x) ) = 2x - 4
Explanation:
In the second step, I replaced every x with h(x). In the next step, I replaced the h(x) on the right hand side with 2x+3. From there I combined like terms.
Since you need an isolated variable to use the substitution method, we need to re-arrange one of the equations. This will probably be easiest to do with the first one.
Add 5y to both sides of the first equation.
x=10+5y
Now, in the second equation, put in 10+5y in any spot that has an x.
2(10+5y)-10y=20
Distribute the 2 to both numbers in the parenthesis.
20+10y-10y=20
Combine like terms.
20=20
This means that the two equations are actually the same. You can see this if you multiply the whole first equation by 2
2(x-5y=10)
2x-10y=20, which is the same as the second equation. Therefore, the two equations are actually the same one.
Answer:
256
Step-by-step explanation:
First, handle the exponent:
2²=4 (2*2=4) and 4³=64 (4*4=16*4=64)
Now multiply those two outcomes:
4*64=<u>256</u>
This equation is also known as 4⁴
Formula
A=bh divides by 2
SUBSTITUTE
45=b9 divided by 2
MULTIPLY/DIVIDE
You can either divide by 2 or multiply by 1/2 (gets the same answer)
9 x 1/2 = 4.5
DIVIDE
45 divides by 4.5 = 10
CHECK
A= 10 x 9 divided by 2 or multiply by 1/2 (same answer) = 45
Thus, the answer is 10.
I hope this helped you understand the process!
Answer:
17/60
Step-by-step explanation: